Pengembangan Aplikasi Presensi Dengan Integrasi Titik Koordinat dan Foto Untuk Meningkatkan Efisiensi Manajemen Kehadiran (Studi Kasus : CV. Canvas Bandung) - Uro Abdurohim; Josandi Ruhansyah; Haris Gunawan (LPPM STMIK Bandung, 2024)
Employee non-compliance with company regulations is a common issue at Canvas Bandung. This can occur due to weak oversight of human resources, in this case, the employees. To find a solution to this ongoing problem, a system is needed to assist supervisors in monitoring employee compliance with organizational regulations. To address this challenge, the author has developed an attendance application integrated with a location tracking system and image capture to enable more accurate monitoring. The development of this attendance system is expected to improve employee compliance with company regulations and assist supervisors in better managing human resources.